Acupuncture combined with methylcobalamin for the treatment of chemotherapy-induced peripheral neuropathy in patients with multiple myeloma. Issue 1 (December 2017) - Han, Xiaoyan; Wang, Lijuan; Shi, Hongfei; Zheng, Gaofeng; He, Jingsong; Wu, Wenjun; Shi, Jimin; Wei, Guoqing; Zheng, Weiyan; Sun, Jie; Huang, He; Cai, Zhen
Abstract Background Chemotherapy-induced peripheral neuropathy (CIPN) seriously affects the quality of life of patients with multiple myeloma (MM) as well as the response rate to chemotherapy. Acupuncture has a potential role in the treatment of CIPN, but at present there have been no randomized clinical research studies to analyze the effectiveness of acupuncture for the treatment of CIPN, particularly in MM patients. Methods The MM patients (104 individuals) who met the inclusion criteria were randomly assigned into a solely methylcobalamin therapy group (500 μg intramuscular methylcobalamin injections every other day for 20 days; ten injections) followed by 2 months of 500 μg oral methylcobalamin administration, three times per day) and an acupuncture combined with methylcobalamin (Met + Acu) group (methylcobalamin used the same way as above accompanied by three cycles of acupuncture). Of the patients, 98 out of 104 completed the treatment and follow-ups. There were 49 patients in each group. The evaluating parameters included the visual analogue scale (VAS) pain score, Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (Fact/GOG-Ntx) questionnaire scores, and electromyographic (EMG) nerve conduction velocity (NCV) determinations. We evaluated the changes of the parameters in each group before and after the therapies and made a comparison between the two groups. Results After 84 days (three cycles) of therapy, the pain was significantly alleviated in both groups, with a significantly higher decrease in the acupuncture treated group (P < 0.01). The patients' daily activity evaluated by Fact/GOG-Ntx questionnaires significantly improved in the Met + Acu group (P < 0.001). The NCV in the Met + Acu group improved significantly while amelioration in the control group was not observed. Conclusions The present study suggests that acupuncture combined with methylcobalamin in the treatment of CIPN showed a better outcome than methylcobalamin administration alone. Trial registration China Clinical Trials Register (registration no.ChiCTR-INR-16009079, registration date August 24, 2016).